Follow-up magnetic resonance imaging/3D-magnetic resonance cholangiopancreatography in patients with primary sclerosing cholangitis: challenging for experts to interpret - Zenouzi, R; Liwinski, T; Yamamura, J; Weiler-Normann, C; Sebode, M; Keller, S; Lohse, A; Schramm, C; International Psc Study Group (Ipscsg), (Wiley, 2018)
Background: In patients with primary sclerosing cholangitis follow‐up magnetic resonance imaging (MRI) with magnetic resonance cholangiopancreatography (MRCP) is performed by many centres, particularly for the early detection of biliary malignancies and strictures. Clinically meaningful MRI‐based definitions of primary sclerosing cholangitis related complications are, however, lacking. Aim: To investigate how primary sclerosing cholangitis experts interpret follow‐up MRI/MRCP with a focus on conclusions that may impact clinical decision‐making in primary sclerosing cholangitis. Methods: Within the International Primary Sclerosing Cholangitis Study Group, an online survey on 16 real‐life primary sclerosing cholangitis cases including clinical and biochemical information as well as a T2‐weighted liver MRI/3D‐MRCP was conducted. The interpretation of images and subsequent recommendations were assessed using a multiple‐choice questionnaire. An inter‐rater reliability calculation (Fleiss′ kappa) was performed and factors potentially affecting the interpretation of magnetic resonance images were analysed using generalised linear mixed‐effect models. Results: Forty‐four members/associates of the International Primary Sclerosing Cholangitis Study Group (median experience in the care of primary sclerosing cholangitis patients: 14 years) completed the survey. The MRI interpretation significantly varied among the participants. The lowest agreement was found with respect to the indication to perform subsequent endoscopic retrograde cholangiopancreatography (ERCP; Κ = 0.12, 95%CI 0.11‐0.14). Elevated total bilirubin was the variable with the strongest effect on the rate of suspected dominant strictures, cholangiocarcinoma or ERCP recommendations. Liver cirrhosis did not prevent participants from recommending ERCP. Overall, the survey participants′ recommendations contrasted the real‐life management and outcome. Conclusions: In primary sclerosing cholangitis, the interpretation of follow‐up MRI/3D‐MRCP significantly varies even among experts and seems to be primarily affected by bilirubin levels. Generally accepted MRI‐based definitions of primary sclerosing cholangitis‐related complications are urgently needed.